PENGARUH POSISI PICK UP COIL DENGAN PUTARAN MESIN TERHADAP KONSUMSI BAHAN BAKAR PADA MESIN 150 CC - Surbakti, Adnan (Jurnal Sistem Informasi Kaputama (JSIK), 2021)
The purpose of this study was to determine how much influence changes in pickup coil and engine speed on fuel consumption in a 150 cc engine. The method used in this study is the experimental method or direct experimental method by varying the pickup coil position and engine speed. There are several conclusions from this research, namely: 1) The higher the engine speed for each time advancing the pickup coil position forward 1mm, forward 2 mm , and going forward 3 mm more wasteful of fuel consumption. 2) Compared to the position of standard pick up coil with 1mm, 2mm, and 3mm pick up coil, the fuel consumption is more wasteful. 3) Comparison between the 2mm and 1mm pickup coil times is more wasteful of fuel consumption than the standard pickup coil positions. 4) Compared between the 1 mm backward pickup coil with the standard condition, the fuel consumption is more efficient when the pickup coil retreated by 1 mm. 5) At the time of retreating the pick up coil the higher the motor rotation, the more efficient fuel consumption.